2012
DOI: 10.1100/2012/126723
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Sensitive Gels for Intratumoral Delivery ofβ-Lapachone: Effect of Cyclodextrins and Ethanol

Abstract: This work evaluated the potential of Pluronics (varieties F127 and P123) in combination with solubilizing agents to be used as syringeable in situ gelling depots of intratumoral β-lapachone (βLAP). Pluronic dispersions prepared at various concentrations in the absence and the presence of ethanol and randomly methylated β-cyclodextrin (RMβCD) were characterized regarding their rheological properties, drug solubilization capacity, and in vitro release. Pluronic F127 (18–23%) formulations combined high ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Pluronic® F127 or poloxamer 407 and Gelucire 44/14 were also used as amphiphilic excipients that can act as solubilising agents. Pluronic® F127 is a non-ionic tri-block copolymer of polyoxyethylene(PEO)-polyoxypropylene(PPO)-polyoxyethylene (PEO) [24] with an HLB value of 22 [25]; this material is considered to be non-irritant and non-sensitising in topical and transdermal applications [26][27]. Gelucire® 44/14, with HLB value of 14, is a mixture of monoesters, diesters and triesters of glycerol, and monoesters and diesters of polyethylene glycols [28] that belongs to the lauryl polyoxylglycerides (macroglycerides) family.…”
Section: Introductionmentioning
confidence: 99%
“…Pluronic® F127 or poloxamer 407 and Gelucire 44/14 were also used as amphiphilic excipients that can act as solubilising agents. Pluronic® F127 is a non-ionic tri-block copolymer of polyoxyethylene(PEO)-polyoxypropylene(PPO)-polyoxyethylene (PEO) [24] with an HLB value of 22 [25]; this material is considered to be non-irritant and non-sensitising in topical and transdermal applications [26][27]. Gelucire® 44/14, with HLB value of 14, is a mixture of monoesters, diesters and triesters of glycerol, and monoesters and diesters of polyethylene glycols [28] that belongs to the lauryl polyoxylglycerides (macroglycerides) family.…”
Section: Introductionmentioning
confidence: 99%
“…From the results obtained, the average gelation temperature and gelation time decrease as the concentration of Pluronic F-127 increases, which leads to higher concentration of PPO responsible for the gelation effect. Based on the literation, lower Pluronic F-127 concentration can form a gel at a longer time; however, a concentration above 22% of Pluronic F-127 becomes gel at room temperature that is not considerable for spray formulation [ 32 , 33 ]. The requirement for the gelation temperature of the base formulation was set between 29 °C and 35 °C, and the gelation time was set at less than 2.30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Although drug administration into the nose is often performed using a pipette or a polyethylene tube attached to a microsyringe/micropipette (41,42), herein we preferred to use the MicroSprayer ® Aerosolizer and to load zonisamide in an in situ-gelling hydrogel, the Pluronic F-127 vehicle. This choice was based on our recent studies that demonstrated that almost 50% of levetiracetam undergoes direct nose-tobrain delivery after its nasal administration (23,(41)(42)(43)(44)(45). Nonetheless, to increase in situ-gelling properties and m u c o a d h e s i o n , C a r b o p o l ® 9 7 4 P a n d N o v e o n ® Polycarbophil polymers were herein investigated and subjected to cellular viability tests to select the safest one for IN administration to mice.…”
Section: Discussionmentioning
confidence: 99%